2009
DOI: 10.3928/00904481-20090508-02
|View full text |Cite
|
Sign up to set email alerts
|

An 11-month-old Girl with High Fever

Abstract: <div class="ftContainer"> <style> ol{ list-style-type:none; } </style> <div class="ftAuthorNotes"> <p>Tugba Erener Ercan, MD; Gokmen Ercan, MD; and Muhsin Arpaozu, MD, are with Maltepe University Medical Faculty, Department of Pediatrics, Istanbul, Turkey. </p> <p>Dr. Tugba Erener Ercan; Dr. Gokmen Ercan; and Dr. Arpaozu have disclosed no relevant financial relationships.</p> <p>Address correspondence to: Tugba Erener Ercan, MD, Maltepe Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…They showed that this sign appears in the early stage of the disease, between 1 and 4 days after the onset of the illness by fever (3). Similar finding was reported by Hsu et al in 1986 and others (1,8,16). …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…They showed that this sign appears in the early stage of the disease, between 1 and 4 days after the onset of the illness by fever (3). Similar finding was reported by Hsu et al in 1986 and others (1,8,16). …”
Section: Discussionsupporting
confidence: 92%
“…Also, thrombocytopenia is unusual in KD, but it is considered as a risk factor for the development of aneurism(33). In this review, among supplementary laboratory findings to diagnosing KD in patients with BCGitis we found elevated CRP more than 3 mg (8,14,16,26), increased ESR more than 40 mm/h (8,13,16,26), elevated alanine aminotransferase (1,14), Leukocytosis (13,14), normochromic, normocytic anaemia (13,16,26), sterile pyuria more than 10 white blood cell/mm 3 (1,8,22), thrombocytosis and thrombocytopenia (1,8,16,21-24,26). …”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations